Impact of the nationalization of hydrocarbons on natural gas exports and bolivia’s gdp, period 1996-2012 - Foronda Monasterios, Eddy Ángel (2022)
In recent decades, the hydrocarbon sector has taken on vital importance in the Bolivian economy, especially natural gas, since it constitutes a good source of income for the State. For this reason, this article analyzes whether the increase in exports of natural gas volumes and foreign direct investment had a positive result in the economic growth of Bolivia. Likewise, it is determined how the nationalization of hydrocarbons, in 2006, had a positive or negative impact on the Bolivian economy. For this, first, unit root tests were applied, then statistical cointegration tests and error correction vectors were estimated to determine the existence of a long-term relationship and the possible causality between the variables. In this way, the estimates show a long-term relationship between GDP, FDI, the export of natural gas and the sale price of natural gas, however, there are no short-term effects. In particular, natural gas exports and FDI do not show causality on GDP. Finally, it is shown that nationalization caused a negative structural change in Bolivia’s economic growth.